4(2x-3)-4x=3(2x-6)

Simple and best practice solution for 4(2x-3)-4x=3(2x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-3)-4x=3(2x-6) equation:


Simplifying
4(2x + -3) + -4x = 3(2x + -6)

Reorder the terms:
4(-3 + 2x) + -4x = 3(2x + -6)
(-3 * 4 + 2x * 4) + -4x = 3(2x + -6)
(-12 + 8x) + -4x = 3(2x + -6)

Combine like terms: 8x + -4x = 4x
-12 + 4x = 3(2x + -6)

Reorder the terms:
-12 + 4x = 3(-6 + 2x)
-12 + 4x = (-6 * 3 + 2x * 3)
-12 + 4x = (-18 + 6x)

Solving
-12 + 4x = -18 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-12 + 4x + -6x = -18 + 6x + -6x

Combine like terms: 4x + -6x = -2x
-12 + -2x = -18 + 6x + -6x

Combine like terms: 6x + -6x = 0
-12 + -2x = -18 + 0
-12 + -2x = -18

Add '12' to each side of the equation.
-12 + 12 + -2x = -18 + 12

Combine like terms: -12 + 12 = 0
0 + -2x = -18 + 12
-2x = -18 + 12

Combine like terms: -18 + 12 = -6
-2x = -6

Divide each side by '-2'.
x = 3

Simplifying
x = 3

See similar equations:

| 86=21-13x | | 2x+19=5x+4 | | 4(2x-3)-4x=3x-4 | | x(x+3)=(x-2)(x-4) | | 4(2x-3)-4x=4x-12 | | 6w^2-1=0 | | 2900-p=64 | | 2x^2+16x+32=24 | | 12x-44=7x+13 | | 2x-3yi=-14+9i | | .36(12)+.06x=.18(12+x) | | 7z^2-7z+1=0 | | 5y-[-(2-3y)+4]=-9y-[-(1+4y)-8]+2 | | Y-2714=3601 | | -16=n-16 | | 48-5/4 | | 8f^2-8=0 | | x/-11-3 | | 5*(x-3)+7= | | -20m=220 | | 4t^2-2t-8=0 | | 6t-t-3=4t-5 | | 2n+1=-98 | | x^2-13x+120=0 | | -(4xy-9)+2(3xy+4)= | | 3x+x-7=3x+3 | | 3-5/2x/5x+7/4x^2 | | 12x-7+4x=5x+3x-7 | | 3n-1-(n-4)-[2(n-3)-3(1-2n)]=-n-2 | | 3/5w+9=-1 | | x+x+4+x+4=44 | | 2g^2+9g+7=0 |

Equations solver categories